Photos of the conference - Åhman, Birgitta (Rangifer, 1984)
Birgitta  Åhman is the photographer of the series of pictures from the conference, also for the cover photo of the full paper edition showing Kongsvold Mountain Hut and Biological Station.
Keywords: photos